2019
DOI: 10.1093/rheumatology/kez163
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between citations, downloads and alternative metrics in rheumatology publications: a bibliometric study

Abstract: Objective Scientific journals and authors are frequently judged on ‘impact’. Commonly used traditional metrics are the Impact Factor and H-index. However, both take several years to formulate and have many limitations. Recently, Altmetric—a metric that measures impact in a non-traditional way—has gained popularity. This project aims to describe the relationships between subject matter, citations, downloads and Altmetric within rheumatology. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 17 publications
0
12
0
3
Order By: Relevance
“…The study designs of the included articles were mixed research designs [ 15 – 28 , 30 – 32 ] and randomized controlled trials [ 11 , 29 ]. The research fields of these articles included biomedicine [ 20 ], burn care [ 31 ], ecology and conservation [ 30 ], emergency medicine [ 19 ], engineering and technology, gastroenterology and hepatology [ 26 ], general medicine [ 18 ], joint arthroplasty [ 29 ], medical education [ 15 ], medical and natural sciences [ 25 ], multidisciplinary [ 22 ], oncology [ 24 ], physiotherapy [ 11 , 16 ], plastic surgery [ 17 ], psychiatry [ 23 ], radiology [ 32 ], rheumatology [ 21 ], social sciences and humanities, solid organ transplantation [ 27 ], and spine [ 28 ]. The main objective of the included studies was to assess the association between Altmetric scores and variables such as citation counts (i.e., number of citations), journal impact factor, access counts (considered the sum of HTML views and PDF downloads), papers published as open access, time since publication, and/or press releases generated by the publishing journal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study designs of the included articles were mixed research designs [ 15 – 28 , 30 – 32 ] and randomized controlled trials [ 11 , 29 ]. The research fields of these articles included biomedicine [ 20 ], burn care [ 31 ], ecology and conservation [ 30 ], emergency medicine [ 19 ], engineering and technology, gastroenterology and hepatology [ 26 ], general medicine [ 18 ], joint arthroplasty [ 29 ], medical education [ 15 ], medical and natural sciences [ 25 ], multidisciplinary [ 22 ], oncology [ 24 ], physiotherapy [ 11 , 16 ], plastic surgery [ 17 ], psychiatry [ 23 ], radiology [ 32 ], rheumatology [ 21 ], social sciences and humanities, solid organ transplantation [ 27 ], and spine [ 28 ]. The main objective of the included studies was to assess the association between Altmetric scores and variables such as citation counts (i.e., number of citations), journal impact factor, access counts (considered the sum of HTML views and PDF downloads), papers published as open access, time since publication, and/or press releases generated by the publishing journal.…”
Section: Resultsmentioning
confidence: 99%
“…Different types of analyses were conducted in the included studies: correlation analysis [ 15 , 17 19 , 22 , 23 , 26 – 29 , 31 , 32 ], regression analysis [ 11 , 16 , 21 ], boosted regression trees analysis [ 30 ], principal component analysis, and factor analysis [ 20 , 25 ]. The main results of the included studies demonstrated that the variables citation counts (i.e., number of citations), journal impact factor, access counts (considered the sum of HTML views and PDF downloads), papers published as open access, time since publication, and press releases generated by the publishing journal were associated with Altmetric scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found associations between social media activity and citation levels, 4 7 8 while others could not confirm this. 9 10…”
Section: Connection Between Altmetrics and Citationsmentioning
confidence: 99%
“…An analysis using data from manuscripts published from 2010 to 2015 in Rheumatology did not find a connection between the Altmetric score and citation rate. 9 This discrepancy could be due to the analysis of different journals, more probable however, due to the increasing usage of social media by Rheumatologists in recent years. A survey among young Rheumatologists in 2016/2017 showed that more than 80% were active social media users 13 and during the EULAR meeting 2018 #EULAR2018 was used by over 10 000 tweets.…”
Section: Connection Between Altmetrics and Citationsmentioning
confidence: 99%